Design of Antibacterial Agents: Alkyl Dihydroxybenzoates against Xanthomonas citri subsp citri - Nazare, Ana Carolina [UNESP]; Polaquini, Carlos Roberto [UNESP]; Cavalca, Lucia Bonci [UNESP]; Anselmo, Daiane Bertholin [UNESP]; Calmon Saiki, Marilia de Freitas [UNESP]; Monteiro, Diego Alves [UNESP]; Zielinska, Aleksandra; Rahal, Paula [UNESP]; Gomes, Eleni [UNESP]; Scheffers, Dirk-Jan; Ferreira, Henrique [UNESP]; Regasini, Luis Octavio [UNESP] (Mdpi, 2018)
Xanthomonas citri subsp. citri (Xcc) causes citrus canker, affecting sweet orange-producing areas around the world. The current chemical treatment available for this disease is based on cupric compounds. For this reason, the objective of this study was to design antibacterial agents. In order to do this, we analyzed the anti-Xcc activity of 36 alkyl dihydroxybenzoates and we found 14 active compounds. Among them, three esters with the lowest minimum inhibitory concentration values were selected; compounds 4 (52 M), 16 (80 M) and 28 (88 M). Our study demonstrated that alkyl dihydroxybenzoates cause a delay in the exponential phase. The permeability capacity of alkyl dihydroxybenzoates in a quarter of MIC was compared to nisin (positive control). Compound 28 was the most effective (93.8), compared to compound 16 (41.3) and compound 4 (13.9) by percentage values. Finally, all three compounds showed inhibition of FtsZ GTPase activity, and promoted changes in protofilaments, leading to depolymerization, which prevents bacterial cell division. In conclusion, heptyl dihydroxybenzoates (compounds 4, 16 and 28) are promising anti-Xcc agents which may serve as an alternative for the control of citrus canker.
Keywords: citrus canker; antimicrobial; plant disease; membrane disruption; phenolic acids